Dynamic alterations in white blood cell counts and SARS-CoV-2 shedding in saliva: an infection predictor parameter - Aghbash, Parisa Shiri; Rasizadeh, Reyhaneh; Shirvaliloo, Milad; Nahand, Javid Sadri; Baghi, Hossein Bannazadeh (Frontiers in Medicine, 2023)
Introduction The recent coronavirus (COVID-19) outbreak posed a global threat and quickly escalated to a pandemic. However, accurate information on potential relationships between SARS-CoV-2 shedding in body fluids, especially saliva, and white blood cell (WBC) count is limited. In the present study we investigated the potential correlation between alterations in blood cell counts and viral shedding in saliva in a cohort of COVID-19 patients. Method In this preliminary clinical research, 24 age-matched COVID-19 patients without comorbidities, 12 (50%) men and 12 (50%) women, were followed up for a period of 5 days to investigate whether changes in the level of viral shedding in saliva might parallel with temporal alterations in WBC count. Viral shedding in saliva was qualitatively measured by performing SARS-CoV-2 rapid antigen tests on patient saliva samples, using SARS-CoV-2 Rapid Antigen Test Kit (Roche, Basel, Switzerland). These patients were classified into two groups with sputum and non-sputum cough. WBCs counts including leukocyte (LYM), neutrophil (NEU), and LYM counts were recorded for each patient on days 1, 3, and 5. Results The results of the present study showed that the levels of WBC, LYM, and NEU as well as erythrocyte sedimentation rate (ESR) increased significantly on the 5th day compared to the first day in both groups with sputum. However, the levels of C-reactive protein (CRP), Neutrophil-to-Lymphocyte Ratio (NLR) and lactate dehydrogenase (LDH) did not show significant changes. Conclusion This study proves that investigating the change in the number of blood LYMs as well as laboratory parameters such as CRP, LDH, and ESR as biomarkers is an accurate indicator to detect the amount of viral shedding in people with sputum and non-sputum. The results of our study denote that the measured parameters exhibit the intensity of viral shedding in people with sputum.